PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di BEI Tahun 2013-2015) - Putri Wulan Sari, 12.05.52.0107; Wahyu Widati, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
The purpose of this study was to influence VACA, VAHU and STVA to financial performance proxied by Return on Assets (ROA) and the market value of the banking company in BEI. The population is a banking company that listing on the Indonesian Stock Exchange (BEI) in the year 2013-2015. The sampling technique used purposive sampling. The criteria for the sample in this study is a company that makes a profit for the year of observation, and the company has a complete data associated with the variables needed in research. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: VACA positive effect on ROA. VAHU and STVA and no significant positive effect on ROA. VACA and VAHU positive and not significant to the market to book value. STVA positive effect on the market to book value.Keywords: Intellectual Capital, Profitability and Market Value